The Correlation Between Personal Reference: Health Workers and Health Facilities with Parenting in Stunting Prevention - Dita Fajrianti; Esti Yunitasari; Retnayu Pradanie (Universitas Airlangga, 2020)
Introduction: The influence of parenting, the scope and quality of health services, the environment, and food are the leading causes of stunting. This study aims to analyze the correlation between personal reference and health facilities with parenting in stunting prevention in Madura East Java.Methods: The design of this study was a cross-sectional study. The population in this study were mothers who had children aged 6-24 months in Madura East Java with 149 mothers and obtained a sample of 109 mothers selected using a purposive sampling technique. The independent variable was the personal reference and health facilities. At the same time, the dependent variable was parenting in stunting prevention. The data were collected using a questionnaire. The questionnaire has been a validity and reliability test. This study was analyzed using the Spearman rho test with a significance level α <0.05.Results: Personal reference have a correlation in parenting in stunting prevention with significance (p=0.017; r=0.228) Health care facilities have a correlation in parenting in stunting prevention with significance (p=0.020; r=0.222)Conclusion: Personal reference and health facilities have a significant role in parenting in stunting prevention. Health workers are expected to be able to provide interventions that are compatible with stunting prevention factors to reduce the incidence of stunting in Indonesia. The more complete health facilities to provide information about pediatric health, the more capable the mother to provide prevention in stunting on children.